Detailed analysis of the Japanese version of the Rapid Dementia Screening Test, revised version. - Moriyama, Yasushi; Yoshino, Aihide; Muramatsu, Taro; Mimura, Masaru (Psychogeriatrics, 2017)
Aim The number-transcoding task on the Japanese version of the Rapid Dementia Screening Test ( RDST-J) requires mutual conversion between Arabic and Chinese numerals (209 to 二百九, 4054 to 四千五十四, 六百八十一 to 681, 二千二十七 to 2027). In this task, question and answer styles of Chinese numerals are written horizontally. We investigated the impact of changing the task so that Chinese numerals are written vertically. Methods Subjects were 211 patients with very mild to severe Alzheimer's disease and 42 normal controls. Mini- Mental State Examination scores ranged from 26 to 12, and Clinical Dementia Rating scores ranged from 0.5 to 3. Results Scores of all four subtasks of the transcoding task significantly improved in the revised version compared with the original version. The sensitivity and specificity of total scores ≥9 on the RDST-J original and revised versions for discriminating between controls and subjects with Clinical Dementia Rating scores of 0.5 were 63.8% and 76.6% on the original and 60.1% and 85.8% on revised version. Conclusions The revised RDST-J total score had low sensitivity and high specificity compared with the original RDST-J for discriminating subjects with Clinical Dementia Rating scores of 0.5 from controls.